2010
DOI: 10.5114/aoms.2010.13907
|View full text |Cite
|
Sign up to set email alerts
|

Original research Risk factors in Central Poland for the development of superficial and nodular basal cell carcinomas

Abstract: Introduction: In the last decades the number of skin carcinomas has dramatically increased, which is mainly connected with changes in lifestyle, especially with common use of artificial light sources such as sunbeds. Basal cell carcinoma (BCC) is the most common form of skin cancer in white populations. Basal cell carcinomas are divided into subtypes, depending on their clinical picture and histology. The main groups are nodular (nBCC) and superficial (sBCC) ones. The major recognized risk factors for basal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
6
18
1
1
Order By: Relevance
“…HDL-C is the beneficial form of blood cholesterol which protects the artery wall from atherosclerosis [43]. Even in individuals whose LDL levels are low, HDL remains a strong independent predictor of coronary artery disease risk [44]. Besides preventing cholesterol accumulation in cells of the artery wall, HDL-C acts as an anti-inflammatory agent by degrading lipid oxidation products [43–47].…”
Section: Discussionmentioning
confidence: 99%
“…HDL-C is the beneficial form of blood cholesterol which protects the artery wall from atherosclerosis [43]. Even in individuals whose LDL levels are low, HDL remains a strong independent predictor of coronary artery disease risk [44]. Besides preventing cholesterol accumulation in cells of the artery wall, HDL-C acts as an anti-inflammatory agent by degrading lipid oxidation products [43–47].…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades an increase of cutaneous malignancies has been shown in various studies [5,6]. In the region of Northern Poland that tendency is also noted [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that differences in Dsg2/Dsg3 profiles in nBCC and sBCC may be due to a different origin of these subtypes. It has even been suggested that BCC should not be treated as a single condition . On the other hand, many BCCs show a mixed histological pattern .…”
Section: Discussionmentioning
confidence: 99%